PENGARUH PENDIDIKAN KEWIRAUSAHAAN, MOTIVASI BERPRESTASI, DAN STATUS SOSIAL EKONOMI ORANG TUA TERHADAP MINAT BERWIRAUSAHA DENGAN SELF EFFICACY SEBAGAI VARIABEL INTERVENING - Antyanadea Maharani; Agus Widarko; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study was to analyze: 1) The direct impact of Entrepreneurship Education on Self Efficacy, 2) The direct impact of Achievement Motivation on Self Efficacy, 3) The direct impact of Socio-Economic Status of Parents on Self Efficacy, 4) The direct impact of Self Efficacy on Entrepreneurial Interest, 5) Indirect impact of Entrepreneurship Education on Entrepreneurial Interest with Self Efficacy as an intervening variable, 6) Indirect impact of Achievement Motivation on Entrepreneurial Interest with Self Efficacy as an intervening variable, 7) Indirect impact of Socio-Economic Status of Parents on Entrepreneurial Interest with Self Efficacy as an intervening variable.The sample in this study used the entire population, namely S1 Management students of the Faculty of Economic and Business, who were taking advanced entrepreneurship courses, totaling 92. The results of this study showed: 1) Entrepreneurship Education has not direct impact on Self Efficacy, 2) Motivation Achievement has a direct impact on Self Efficacy, 3) Socio-Economic Status of Parents has not direct impact on Self Efficacy, 4) Self Efficacy has a direct impact on Entrepreneurial Interest, 5) Entrepreneurship Education has not indirect impact on Entrepreneurial Interest with Self Efficacy as an intervening variable, 6) Achievement Motivation has a indirect impact on Entrepreneurial Interest with Self Efficacy as an intervening variable, 7) Socio-Economic Status of Parents has not indirect impact on Entrepreneurial Interest with Self Efficacy as an intervening variable.Keywords: Entrepreneurship Education, Achievement Motivation, Socio-Economic Status of Parents, Self Efficacy, Entrepreneurial Interest